2023
DOI: 10.1111/dom.15400
|View full text |Cite
|
Sign up to set email alerts
|

Impact of weight loss and weight gain trajectories on body composition in a population at high risk of type 2 diabetes: A prospective cohort analysis

T. Yates,
G. J. H. Biddle,
J. Henson
et al.

Abstract: AimIn a primary care population at high risk of type 2 diabetes, 24‐month weight change trajectories were used to investigate the impact of weight cycling on fat mass (FM) and fat‐free mass (FFM).Materials and MethodsCohort data from the Walking Away from Type 2 Diabetes trial was used, which recruited adults at‐risk of type 2 diabetes from primary care in 2009/10. Annual weight change trajectories based on weight loss/gain of ≥5% were assessed over two 24‐month periods. Body composition was measured by bioele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Body weight and adiposity gains in weight cycling mice were nonsignificant when compared with high-fat-diet-fed mice that did not undergo weight cycling, and there were also gender difference [ 19 ]. The effect of weight cycling on body fat is also related to physical status, and a study of patients with type 2 diabetes found that in overweight and obese patients with type 2 diabetes, weight cycling may result in a relative loss of free fat mass or an increase in fat mass [ 20 ].…”
Section: Effects Of Weight Cycling On Tissues and Organsmentioning
confidence: 99%
“…Body weight and adiposity gains in weight cycling mice were nonsignificant when compared with high-fat-diet-fed mice that did not undergo weight cycling, and there were also gender difference [ 19 ]. The effect of weight cycling on body fat is also related to physical status, and a study of patients with type 2 diabetes found that in overweight and obese patients with type 2 diabetes, weight cycling may result in a relative loss of free fat mass or an increase in fat mass [ 20 ].…”
Section: Effects Of Weight Cycling On Tissues and Organsmentioning
confidence: 99%